Karakterisasi Varietas Kedelai Berbasis Impedansi dan Hubungannya dengan Daya Tumbuh Benih: Lia Agustina, Melania Suweni Muntini - Lia Agustina, Lia Agustina; Melania Suweni Muntini, Melania Suweni Muntini (Jurnal Fisika dan Aplikasinya, 2025)
Characterization of soybean varieties through impedance measurement that can be used to distinguish between high-quality soybean seed and of low quality has been performed. Impedance measurement using a probe is connected to LCR meter. Soybean seeds were characterized in this study are varieties Anjasmoro, Argomulyo, Burangrang and Panderman are each classified into normal soybean seeds, young soybeans, soybean infected with the virus. The results obtained from this study is the difference in impedance value of the four varieties. The largest impedance value is obtained from varieties Argomulyo for normal soybean seed is 20.110 MO, young soybean varieties Argomulyo to 7.750 MO. For soybeans infected with the virus, a large impedance value at Anjasmoro varieties is 9.234 MO. The percentage of the growing power obtained by normal soybean seed with a percentage of 100% for each variety, young soybeans that is 4% for the entire seed varieties Anjasmoro and die for other varieties, in soybean infected with the virus for Anjasmoro varieties have a percentage of 80%, Argomulyo varieties have a percentage of 40%, Burangrang varieties have a percentage of 16% and Panderman varieties have a percentage of 32%. In this study which tested is the growing power of soybean seed, but for the productivity of the crop has not been performed testing.